ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2014 - Murni, Yetty; Freddy, Hotman; Safitri, Yulia (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2016)
Earnings management is the actions taken by management to affecting earnings report for a particular purpose. Earnings management practices are influenced by conflicts of interest between management and owners when all parties are trying to reach and maintain the desired level of prosperity. This study aimed to analyze the factors that influence earnings management. The independent variables used were firm size, leverage, and profitability. The dependent variable used is earnings management. The method used in this study is multiple linear regression analysis with secondary data sourced from Indonesia Stock Exchange (IDX). The samples used in this study were 50 manufacturing companies listed on the Indonesia Stock Exchange from 2012 to 2014. The results of this study showed that the firm size have a significant positive influences on earnings management, but leverage and profitability didn’t have influence on earnings management.